Keseimbangan Investasi Berbasis Imbalan dalam Memediasi Keputusan Pendanaan Badan Usaha Milik Desa (BUMDes) di Karesidenan Pati Indonesia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Village-Owned Enterprises (BUMDes) are established to support the improvement of the local economy. One of the recurring challenges faced by BUMDes is capital availability, which is essential for business expansion and achieving shared objectives. This study aims to analyze the effect of cognitive bias on investment decisions through reward-based investment balance as a mediating variable. The study employed a sample of 165 BUMDes distributed across the Pati Residency, using a combination of purposive sampling and cluster sampling, where the selected BUMDes represented each district and involved investors from the local community or community groups. Data were collected from BUMDes located in five districts within the Pati Residency, and the analysis was conducted using SMART PLS. The results indicate that cognitive bias has a direct and significant effect on community investment decisions as well as on reward-based investment balance. Furthermore, reward-based investment balance was found to have a direct effect on investment decisions. The findings also confirm that reward-based investment balance mediates the relationship between cognitive bias and investment decisions.